The Advantages and Disadvantages of E-working: An Examination using an ALDINE Analysis - Michal Beňo (Emerging Science Journal, 2021)
Objectives: Working remotely comes with significant pros and cons with different demands for individuals or teams. E-working has been the object of much interest, but there has been little research on the statistical difference between its advantages and disadvantages. Research Question: Is there a significant statistical difference between them? Methods: The present research, however, goes one step further and identifies the statistical difference between them. Firstly, we evaluated the positive and negative aspects with a meta-analysis of 20 studies and, secondly, we used a non-parametric test, namely the Wilcoxon Rank Test, for further analysis across pros and cons. Findings: We found that e-working provides more positive than negative ones. A binomial test showed that most studies (more than 50%) mention flexibility, productivity and efficiency, satisfaction and WLB as benefits. Novelty/improvement:E-working is a triple win option. There are many advantages to working remotely, but this method of work does not suit everyone. Our results provide building blocks for a more complete theoretical and practical treatment of e-working for the future. But COVID-19, technology advancement and a connected global world show clearly that e-working will play a crucial role in the future of the workplace. Doi: 10.28991/esj-2021-SPER-02 Full Text: PDF